Improved Efficiency of Pomegranate Seed Oil Administrated Nasally - Hiba Natsheh; Elka Touitou (MDPI AG, 2022)
Pomegranate seed oil (PSO) is currently administrated orally as a food supplement for improving memory. However, the efficiency of the oral dosage forms for such purposes is low, mainly due to the blood brain barrier impeding a good delivery to brain. In this work, we designed and characterized a PSO phospholipid oily gel for nasal administration. We tested the performance of the new PSO delivery system in animal models for impaired memory and locomotor activity. The experimental results indicated a statistically significant improvement (p < 0.05) of more than 1.5 fold in the behavior of animals treated nasally, in comparison to those treated with orally administrated oil. Furthermore, in multiphoton microscopy and near infrared imaging studies, the nasal administration of fluorescent probes, fluorescein isothiocyanate (FITC), and indocyanine green (ICG) incorporated in the PSO system showed enhanced delivery to the brain. Results of the histopathologic examination of the nasal cavity and mucosa, as carried out by a pathologist, indicated the safety of the PSO phospholipid oily gel. In conclusion, the results of this work encourage further investigation of the phospholipid oily gel composition as a new way of PSO administration.